Determinants of gross income from carp production in Bara district, Nepal - Bhandari, Subash; Jha, Dilip Kumar; Shrestha, Amrit; Sapkota, Bina; Bhattarai, Chandan; Rijal, Swodesh; Pokhrel, Subodh (Journal of Agriculture and Natural Resources, 2021)
A study was conducted from March to June 2020 to analyze the determinants of gross income from carp production in the Bara district of Nepal. Altogether, 90 carp producers, 45 each from Simraungadh and Pachrauta municipality in equal basis were sampled by using cluster sampling technique. Primary information was collected through a pre-tested semi-structured interview-based schedule while secondary information was collected reviewing the relevant publications. Data was entered in SPSS 25 and analyzed using STATA 12.1. The results revealed that the cost of labor, cost of feed, assistances and services, and training had significant positive effect on gross income from carp prodcuiton. Furthermore, lack of quality inputs was identified as the most severe production problems whereas Dhalta to be given was recognized as the most severe marketing problems. Thus, encouraging the carp producer to manage the cost of labor and cost of feed deliberately, rationally providing the assistance and services and strengthening the skills and knowledge of producer through training could significantly increase gross income from carp production.